Effects of eating disorders on oral fungal diversity - Back Brito, Graziella Nuernberg [UNESP]; da Mota, Adolfo Jose; de Souza Bernardes, Luciano Angelo; Takamune, Silvia Satomi; Gomes Barbosa Prado, Eliane de Fatima; Cordas, Taki Athanassios; Balducci, Ivan [UNESP]; da Nobrega, Francisco Gorgonio [UNESP]; Koga-Ito, Cristiane Yumi [UNESP] (Elsevier B.V., 2012)
Background. The eating disorders anorexia and bulimia nervosa can cause several systemic and oral alterations related to poor nutrition and induced vomiting; however, the oral microflora of these patients is poorly studied.Objective. The aim of this study was to evaluate fungal microflora in the oral cavity of these patients by culture-dependent and culture-independent methods.Study Design. Oral rinse samples were cultured to assess the prevalence of Candida species, and the isolates were identified by API system. Microorganism counts were compared by the Mann-Whitney test (5%). Ribotyping, a type of molecular analysis, was performed by sequencing the D1/D2 regions of 28S rRNA.Results. Our results demonstrated that the eating disorder group showed higher oral Candida spp. prevalence with culture-dependent methods and higher species diversity with culture-independent methods.Conclusions. Eating disorders can lead to an increased oral Candida carriage. Culture-independent identification found greater fungal diversity than culture-dependent methods. (Oral Surg Oral Med Oral Pathol Oral Radiol 2012;113:512-517)